Susana Polac. La búsqueda del camino interior - Quintana Flores, Moisés Alejandro (2023)
Susana Polac is recognized at the Faculty of Art and Design as the first graduate of the Curriculum for Artists implemented in 1940. However, little is known about her performance as a student at the Academy of Catholic Art. Nor her contribution as a teacher at the beginning of this institution. And even less his recognition by local critics as an emerging artist, with two individual exhibitions held in Lima, before his return to Europe in 1950. This research adds to the recent recognition of his figure as an artist who came to have significance in the renewal of religious art integrated into modern Spanish architecture in the second half of the 20th century. The frieze Glorification of Martyrdom, which she carved for the Church of San Pedro Martir, Theologate of the Dominican Monastery in Alcobendas, Madrid, allows us to establish a relationship between her training as a dancer and her sculptural work.